Lexico-Semantic Errors in Indonesian EFL Students' Argumentative Writing: Types, Causes, and Pedagogical Implications - Rossy Halimatun Rosyidah; Siti Latifatul Rosidah; Lida Holida Mahmud; Nahoras Bona Simarmata (PANOPTICON: Journal of English Studies, 2026)
Academic writing requires not only grammatical accuracy but also appropriate and precise word choice. However, many English as a Foreign Language (EFL) students experience lexico-semantic difficulties that reduce the clarity, accuracy, and naturalness of their academic writing. This study aimed to identify the types of lexico-semantic errors in Indonesian EFL students’ argumentative essays, investigate the factors contributing to these errors, and discuss their pedagogical implications. A descriptive qualitative design was employed. The data consisted of 35 argumentative essays comprising approximately 10,500 words written by undergraduate students at Universitas Pamulang. Semantic errors were identified through document analysis and verified using the Oxford Advanced Learner’s Dictionary (OALD) and academic writing references. Semi-structured interviews with 10 students were conducted to explore the underlying causes of the identified errors. The findings revealed 125 lexico-semantic errors classified into five categories: inappropriate word choice (38.4%), collocation errors (25.6%), literal translation (17.6%), misuse of synonyms (10.4%), and misuse of polysemous words (8.0%). The interviews indicated that first-language interference, limited academic vocabulary, and insufficient awareness of English collocations were the main contributing factors. These findings suggest that academic writing instruction should integrate contextualized vocabulary learning, collocation awareness, and semantic competence to improve students’ lexical accuracy and writing quality.